2014
DOI: 10.1186/1472-6882-14-446
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of the jararhagin toxin on B16F10 murine melanoma

Abstract: BackgroundMalignant melanoma is a less common but highly dangerous form of skin cancer; it starts in the melanocytes cells found in the outer layer of the skin. Jararhagin toxin, a metalloproteinase isolated from Bothrops jararaca snake venom acts upon several biological processes, as inflammation, pain, platelet aggregation, proliferation and apoptosis, though not yet approved for use, may one day be employed to treat tumors.MethodsB16F10 murine melanoma cells were treated with jararhagin (jara), a disintegri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
16
0
3
Order By: Relevance
“…Previous trials have reported that snake venoms are able to act on the tumor in some models, such as melanoma (B16F10 cells) [21], breast (MCF-7 cells) [22], colon (HCT116 and HT-29 cells) [23], lung cancer (NCL-H460 cells) [24], and neuroblastoma (SK-N-MC and SK-N-SH cells) [25]. However, despite these data, there are few studies relating to Bothrops in cervical cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials have reported that snake venoms are able to act on the tumor in some models, such as melanoma (B16F10 cells) [21], breast (MCF-7 cells) [22], colon (HCT116 and HT-29 cells) [23], lung cancer (NCL-H460 cells) [24], and neuroblastoma (SK-N-MC and SK-N-SH cells) [25]. However, despite these data, there are few studies relating to Bothrops in cervical cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated using jararhagin inactivated with 10 mM 1,10-phenanthroline [31]. Thereby, it is probable that both baltergin and baltergin-DC are able to interact with surface integrins impairing C2C12 adhesion to coated plate.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Anticancer activities of SVMPs involve pro-inflammatory effect and apoptotic activity. A purified SVMP from Bothrops jararaca , Jararhagin, interrupted cancer cell adhesion and exhibited a potent cytotoxic effect on melanoma cells 21 via an increase in caspase-3 and anti-proliferative activities 22 . A metalloproteinase from Trimeresurus stejnegeri venom, TSV-DM, inhibited cancer cell proliferation and induced morphological changes on ECV304 cells 23 .…”
Section: Snake Venom Metalloproteinases (Svmps)mentioning
confidence: 99%